Vegetables Spices Fermentation Extract Inhibit NAFLD Development by Attenuation of Steatosis through Suppression of C/EBPα and TNFα mRNA Expression - Rachmawati, Ermin; Machdaniar, Maulidya; Kinasih, Larasati Sekar; Sargowo, Djanggan; Syarifuddin, Brillian Putra; Putri, Fayza Cinta Rahmadina; Ismail, Mahrus (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD), characterized by inflammation and steatosis, is one of the metabolic problems that trigger serious complications. Statin is usually used for NAFLD therapy, however, statin intolerance and resistance reduce the effectiveness of NAFLD treatment. Therefore, this study was conducted to develop the phytopharmaca against NAFLD by elucidating the anti-inflammatory and steatosis suppression of vegetable spices fermentation extract (VSFE) in rabbits induced with high-fat diet (HFD).METHODS: Twenty New Zealand White rabbits were determined into 4 groups; which were groups receiving standard diet (SD), HFD, HFD and 100 mg/kgBW VSFE, as well as HFD and 200 mg/kgBW VSFE. mRNA expressions of tumor necrosis factor alpha (TNFα) and CCAAT/enhancer-binding protein alpha (C/EBPα) were evaluated. The TNFα concentration was quantified after protein and RNA isolation. Inflammation and steatosis were observed in liver hematoxylin-eosin-stained preparate using microscope.RESULTS: Macrophage cells and hepatic steatosis showed significant decrease in a drug dependent manner. An effective dose of 200 mg/kgBW decreased C/EBPα and TNFα expression to 0.45±0.32 and 0.72±0.29 (p=0.013 and p=0.002, compared to the HFD group), respectively. TNFα inflammatory cytokine concentrations also responded to the administration of 100 mg/kgBW and 200 mg/kgBW doses, with the value of 31.72±10.40 mg/dL and 48.35±7.15 mg/dL (p=0.009 and p=0.002, compared to the HFD group), respectively.CONCLUSION: VSFE might prevent NAFLD by inhibit steatosis and inflammation through suppression of C/EBPα expression and TNFα expression.KEYWORDS: C/EBPα, TNFα, fermentation, steatosis, NAFLD